TRAINING OF PROFESSIONALS IN THE FIELD OF FORENSIC EXAMINATION: ORGANIZATIONAL ISSUES AND PROSPECTS - Alekseychuk, Viktoriya; Starodubov, Igor (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
The aim of the article is to determine the optimal model and mechanism for training forensic experts to improve their professional level and bring the field of forensic science to a qualitatively new level. Research methods: general scientific methods of cognition were used in writing the article. Results: high-quality training and retraining of forensic experts is important for an independent and objective judiciary, but does not address all basic issues of state expert personnel policy. A number of areas of public life also require professionally organized application of special knowledge and practical skills. Discussion: problems of quality training of forensic experts. To increase the effectiveness of expert activities in Ukraine, along with generally accepted norms and principles, it is advisable to study, analyze and take into account the world experience of expert structures. It follows that for any country it is important to improve the legal regulation of organizational forms of forensic science. In addition, improving the quality of expert services should be ensured by competitive conditions between participants in forensic activities, which is achieved through the active development of independent forensic science. Education of forensic experts - candidates for the position of forensic research institutions of the Ministry of Justice of Ukraine, forensic research institutions, forensic and forensic psychiatric institutions of the Ministry of Health of Ukraine, expert services of the Ministry of Internal Affairs of Ukraine, Ministry of Defense Ukraine, the Security Service of Ukraine and the State Border Guard Service of Ukraine, should not differ from the education of individuals, forensic experts who are not employees of these institutions, should be professional, providing professional training to educational qualification level not lower than a specialist institution. Considering that in order to ensure the appropriate professional level, specialists who are not employees of state specialized institutions and specialists who are employees of research institutions of forensic examinations of the Ministry of Justice of Ukraine must undergo internships in state specialized institutions of the Ministry of Justice of Ukraine. Our professional knowledge, we propose to create the State Academy of Forensic Science of the Ministry of Justice of Ukraine, which would train these specialists.